Research Methodology In Management: Current Practices, Trends, And Implications For Future Research - Scandura, Terri A.; Williams, Ethlyn A. (Academy of Management Journal, 2000)
This study is a comparison of the strategies employed in management research in two periods, 1995–97 and 1985–87. Through a content analysis of articles from the Academy of Management Journal, Admi...